The consumption of aquaculture products in non-Mediterranean Europe - Young J.A. (Marketing of aquaculture products, 1996)
The paper presents an overview of fish consumption in non-Mediterranean Europe with particular emphasis upon the EU component of the region. The single EU market embraces a tremendous diversity of consumption trends in aquaculture products, both within and between constituent countries. Consumption data is reviewed in terms of its emphasis upon aggregate market volumes and contemporary product prices; but this tends not to reveal important sub-regional variations and more importantly, does little to identify consumer behaviours in the component markets. Generally, aquaculture products have enjoyed a favourable consumer perception, like fish as a healthy foodstuff. However aquaculture products increasingly must accommodate demands for additional product attributes, especially in the more Northern EU markets. Whereas in the past, the whole fish or related concepts have been acceptable, market saturation has encouraged diversification into more added value products. Value may be added in a variety of different guises, incorporating different stages of product transformation and delivery through various organizational structures. Aspects of these evolutionary influences on fish consumption are reviewed. It is contended that hitherto the aquaculture sector has been comparatively slow to respond to the contemporary changes sought by consumers, a situation which is likely to change in the future as consumption incorporates new aquaculture species.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)